2021
DOI: 10.3389/fnins.2021.704459
|View full text |Cite
|
Sign up to set email alerts
|

Neural Bases of Brand Reputation Effect on Extension Evaluation: An ERPs Study

Abstract: Brand extension, as a marketing strategy, is frequently utilized by enterprises to produce new products. There exist several critical factors determining its success, such as brand reputation and perceived fit. The present study adopts the event-related potentials (ERPs) method to explore the underlying neural mechanism of the joint influence of the two factors on consumers’ evaluation of brand extension. Specifically, consumers were presented with a brand with corporate social responsibility (CSR) or corporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 90 publications
(120 reference statements)
0
3
0
Order By: Relevance
“…All the stimuli were presented in the center of a computercontrolled monitor (1,024 × 768 pixels, 60 Hz). Based on a recent work by Liu et al (2021), each group of stimuli in the current study employed the formation of a sentence. Specifically, two fixed verbs were adopted to connect among the brand name, activity, and product name, consisting of the five parts: brand (1) + pushed (2) + association activity (3) + launched (4) + product (5) (e.g., "Yili pushed technological innovation and launched T-shirt" or "Yili pushed charitable donation and launched T-shirt").…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All the stimuli were presented in the center of a computercontrolled monitor (1,024 × 768 pixels, 60 Hz). Based on a recent work by Liu et al (2021), each group of stimuli in the current study employed the formation of a sentence. Specifically, two fixed verbs were adopted to connect among the brand name, activity, and product name, consisting of the five parts: brand (1) + pushed (2) + association activity (3) + launched (4) + product (5) (e.g., "Yili pushed technological innovation and launched T-shirt" or "Yili pushed charitable donation and launched T-shirt").…”
Section: Methodsmentioning
confidence: 99%
“…Carlson et al (2016) revealed that the P3 component could predict prosocial motivation and behaviors of participants, and a notable P3 amplitude was found for evaluating highempathy targets than low-empathy targets. Recently, Liu et al (2021) examined the different brain activities when evaluating the distant extension products with different brand reputations, which found the CSR condition elicited larger LPP (P3 family) amplitude than the ability reputation condition. Based on the abovementioned research, because CSR messages are more prosocial and empathetic, we posit that larger P3 amplitudes would be observed in CSR than CC associations and in HE than the LE group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation